The Guatemalan military project : a violence called democracy - Schirmer, Jennifer G. (Pennsylvania studies in human rights., 1998)
In 1999, the Guatemala truth commission issued its report on human rights violations during Guatemala's thirty-six-year civil war that ended in 1996. The commission, sponsored by the UN, estimates the conflict resulted in 200,000 deaths and disappearances. The commission holds the Guatemalan military responsible for 93 percent of the deaths. In The Guatemalan Military Project, Jennifer Schirmer documents the military's role in human rights violations through a series of extensive interviews striking in their brutal frankness and unique in their first-hand descriptions of the campaign against Guatemala's citizens. High-ranking officers explain in their own words their thoughts and feelings regarding violence, political opposition, national security doctrine, democracy, human rights, and law. Additional interviews with congressional deputies, Guatemalan lawyers, journalists, social scientists, and a former president give a full and balanced account of the Guatemalan power structure and ruling system. With expert analysis of these interviews in the context of cultural, legal, and human rights considerations, The Guatemalan Military Project provides a successful evaluation of the possibilities and processes of conversion from war to peace in Latin America and around the world.